Implementasi Metode Kebersamaan dalam Mengatasi Kesenjangan Sosial Antara Guru PNS dan Guru Honorer di SMP Negeri 3 Kampar Kiri Hilir Kabupaten Kampar - Anasrullah, Anasrullah (Komunitas Manajemen Kompetitif, 2017)
Social discourse is indeed a school managerial problem which, with the difference between the honorary teacher and the state teacher, makes the treatment especially welfare or income treatment. Honorary teachers earn relatively smaller incomes when compared to state teachers. This condition becomes an issue and even the state teacher gets a certification allowance while the honorary teacher does not get it. Through this method of togetherness of this research done and expected with the implementation of the method of togetherness will make the social gap decreases. The type of research is action research and based on the results of research known that implementation method of togetherness can overcome the problem of social inequality with co-workers. The data obtained shows that after held measure the level of social interaction of teachers through harmonious method of togetherness then obtained togetherness can overcome the problem of social inequality with co-workers. Keywords: Implementation, method of togetherness and social inequality